The Influence of Teachers' Resilience and Digital Competence on the Effectiveness of Digital Learning Media in Elementary Schools - Roudhoh; Anas Fachruddin; Suci Hidayati; Rini Nafsiati Astuti; Wahid Murni (BASICA, 2025)
This study aims to analyze the influence of teachers' resilience and digital competence on the effectiveness of the utilization of digital learning media in public elementary schools in Malang Regency. The digital transformation in education requires teachers to possess not only technical digital skills but also psychological and spiritual resilience in the face of change. This study uses a quantitative, correlational design and analyzes the data using Partial Least Squares–Structural Equation Modeling (PLS-SEM). Data were collected using a 1–5 Likert-scale questionnaire distributed to elementary school teachers, with a sample of 445. The rowdon sampling technique was chosen to conduct data analysis using the PLS-SEM statistical tool. The results of the study showed that the R Square value was 0.552 (Adjusted R² = 0.541), which means that teacher resilience and digital competence simultaneously were able to explain 55.2% of the variation in the effectiveness of digital learning media utilization. Teacher digital competence had a significant effect on the effectiveness of digital learning media (β = 0.455; t = 4.566; p < 0.05), while teacher resilience showed a lower, statistically insignificant effect in one of the test models (p < 0.05). This finding confirms that digital competence is a dominant factor in increasing the effectiveness of digital learning media, while resilience plays a supporting factor in strengthening teacher readiness to improve the quality of learning in the era of digital transformation. The research results recommend that schools provide digital competency training for teachers that integrates the development of spiritual and psychological resilience values to create effective, adaptive, and sustainable digital learning.